Me [compact disc, unabridged] - John, Elton (Macmillan Audio, 2019)
An official autobiography by the influential music artist includes coverage of his complicated upbringing in a London suburb, his celebrity collaborations, his struggles with addiction, and the establishment of his AIDS Foundation.